Perceived safety benefits, concerns, and utility of advanced driver assistance systems among owners of ADAS-equipped vehicles. (21st March 2018) - Pradhan, Anuj K.; Pulver, Elizabeth; Zakrajsek, Jennifer; Bao, Shan; Molnar, Lisa
Abstract: Objective: There are many unknowns regarding drivers' use and acceptance of advanced vehicle technologies. This research aimed to examine drivers' perceptions of advanced driver assistance systems (ADAS). Methods: This research was conducted using structured interviews and focus groups of owners of vehicles with advanced technologies. Results: Drivers' perceptions about ADAS were mixed, but generally safety was considered to be the greatest value of the systems. There was recognition that the systems may result in overreliance and thus encourage distraction behaviors or other bad driving habits, and participants generally expressed that they were ultimately responsible for the vehicle's operation and needed to be ready to override the system if it failed. Conclusions: The findings indicate that driver characteristics and individual factors may influence perceptions, behaviors, and interactions with safety technology, and this research is a first step toward understanding any influences. Human factors issues related to automated vehicle technologies are critical for design and deployment, including those of trust, acceptance, and understanding of systems.